2013
DOI: 10.1080/13548506.2013.832783
|View full text |Cite
|
Sign up to set email alerts
|

Attributions and self-efficacy for physical activity in multiple sclerosis

Abstract: Self-efficacy is an important predictor of health-related physical activity in multiple sclerosis (MS). While past experiences are believed to influence efficacy beliefs, the explanations individuals provide for these experiences also may be critical. Our objective was to test the hypothesis that perceived success or failure to accumulate 150 min of physical activity in the previous week would moderate the relationship between the attributional dimension of stability and self-efficacy to exercise in the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…We did not collect pre-randomization exercise baseline behavior through diaries or other data potentially predictive of future exercise behaviour that could be used to better characterize our study sample (i.e., cognitive function, MS course, attributions and self-efficacy for exercise 27 and, caregiver support 28 ). Larger scale, powered studies are required to improve our understanding of the potential benefits of web-based exercise interventions and the predictors for adherence with web-based platforms.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…We did not collect pre-randomization exercise baseline behavior through diaries or other data potentially predictive of future exercise behaviour that could be used to better characterize our study sample (i.e., cognitive function, MS course, attributions and self-efficacy for exercise 27 and, caregiver support 28 ). Larger scale, powered studies are required to improve our understanding of the potential benefits of web-based exercise interventions and the predictors for adherence with web-based platforms.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…In other non-IBD studies, perceived SE has been shown to affect physical, psychological, and social functioning in patients with cancer, multiple sclerosis, and diabetes. [20][21][22] High SE has been linked to success in health screening for breast cancer, 23 decreasing fear of childbirth and decreasing preference for cesarean section, 24 smoking cessation, 25 and prevention of eating disorders in adolescents. 26 Because the first study to develop an SE scale specifically targeted towards patients with IBD who require surveillance colonoscopies, the strengths of our study are the high number of patients enrolled, the high response rates to the questionnaires, and the extensive analysis of all the interrelated questions and responses.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that self-efficacy ( Kasser & Kosma, 2012 ; Kosma & Kasser, 2012 ; Nickel et al, 2014 ; Schmitt et al, 2014 ), perceived exercise benefits ( Kosma & Kasser, 2012 ; Suh et al, 2014 ) and positive exercise intentions ( Ginis et al, 2012 ) are associated with exercise participation in people with MS and SCI-related mobility disability. Self-efficacy, resilience and perseverance are overlapping constructs that impact health behaviors ( Pilutti et al, 2014 ; Sinnakaruppan et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%